Effects of nonsocial and circumscribed interest images on neural mechanisms of emotion regulation in autistic adults - Antezana, Ligia; Coffman, Marika C.; DiCriscio, Antoinette Sabatino; Richey, John A. (Frontiers in Behavioral Neuroscience, 2022)
Emotion dysregulation is commonly reported among autistic individuals. Prior work investigating the neurofunctional mechanisms of emotion regulation (ER) in autistic adults has illustrated alterations in dorsolateral prefrontal cortex (dlPFC) activity, as well as concurrent atypical patterns of activation in subcortical regions related to affect during cognitive reappraisal of social images. Whereas most research examining ER in autism has focused on regulation of negative emotions, the effects of regulating positive emotions has been generally understudied. This is surprising given the relevance of positive motivational states to understanding circumscribed interests (CI) in autism. Accordingly, the purpose of this study was to use fMRI with simultaneous eye-tracking and pupillometry to investigate the neural mechanisms of ER during passive viewing and cognitive reappraisal of a standardized set of nonsocial images and personalized (self-selected) CI images. The autistic group demonstrated comparatively reduced modulation of posterior cingulate cortex (PCC) activation during cognitive reappraisal of CI images compared to viewing of CI, although no eye-tracking/pupillometry differences emerged between-groups. Further, the autistic group demonstrated increased PCC connectivity with left lateral occipital and right supramarginal areas when engaging in cognitive reappraisal vs. viewing CI. In autistic adults, CI may be differentially modulated via PCC. Considering the documented role of the PCC as a core hub of the default mode network, we further postulate that ER of CI could potentially be related to self-referential cognition.